Application of Alternative Medicine in Dentistry - Yusuf, Rohma (Current Practice in Medical Science Vol. 11, 2022)
Various types of natural and spiritual healing methods is being practised as Alternative medicine treatments. These treatments can either be practiced individually or in combination with other conventional treatment for the purpose of relaxing mind, body and soul. Alternative medicines are in practice since ancient time and are practiced globally till date. Every country has its own conventional system of health. Presently, Alternative medicine is assimilated in many feilds including dental. Results from few studies conducted has shown significant effect of holistic healing on dental and oral health. This article reviews about impact of alternative medicine in treating dental health and problems associated with it.